(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2018)
As one of the essential elements of life, since ancient times water has been an endless source of proverbs, sayings, aphorisms and maxims transmitted from one generation to the other and enriched by life experience.Although water is a research subject often exploited in psychoanalytic, stylistic and semantic studies, it does not seem to have drawn paremiologists and translation scholars’ attention. For this reason this article will examine the Romanian proverbs that contain the word apă [water] and their French equivalents, from the point of view of their morphologic, syntactic, semantic and prosodic structure. We also aim to establish the similarities and the differences in the mentalities of these two language-cultures that have a common Roman origin. In addition, we provided our own equivalent (in bold in the text) when bilingual or phraseological dictionaries do not record one or when we consider it useful in order to respect the prosody of the Romanian paremiological structure.